Stuprum saevi tyranni: l'Octavia pseudo-senecana e una variante dimenticata della leggenda di Lucrezia - Lentano, Mario (2022)
The pseudo-Seneca's Octavia and a forgotten variant of Lucretia's legend center dot In pseudo-Seneca's Octavia (vv. 300-303), the rape of Lucretia is attributed to a saevus tyrannus who seems to be identified with king Tarquin the Proud instead of his son Sextus Tar - quinius, as happens in the canonical version of the legend. It is a variant that emerges in other late sources (Claudian, John Lydus) and is sometimes attested also in medieval literature. The artide follows the traces of this variant and puts forward some hypotheses on the reasons that may have led the anonymous tragic author to choose it.